Opini Publik Tentang Penggunaan Teknologi Video Asisten Wasit Sebagai Solusi Kompetisi Liga 1 Sepak Bola Indonesia - Vanny Adriani; Deddy Irwandy (LUGAS Jurnal Komunikasi, 2020)
The use of video assistant referees (VAR) is one solution to football problems in Indonesia. Indonesian football has a problem for years, namely the problem of trust in referees due to many referee bribery scandals and others. Based on this problem, this research focuses on public opinion toward VAR technology use in football. The research methodology is descriptive research, and this research is directed to make careful and detailed observations of the observed phenomena. This descriptive study aims to highlight current issues or problems through a data collection process that allows the researcher to describe the situation more fully than is possible without using this method. Researchers also seek to see phenomena related to technology involvement in sports activities from the players, organizers, spectators, and other stakeholders. The research results found that Public Opinion is formed into three types, for the first type who has a very high level of identification with the football club who is dissatisfied with the use of Video Assistant Referee Technology (VAR), the second type of public who enjoy football matches with debate in a football match less satisfied with the use of Video Assistant Referee (VAR) technology, and the third type for the more modern public sees the use of Video Assistant Referee (VAR) technology as a solution in decisions used in the Indonesian Football League  Competition.